2006
DOI: 10.1002/adfm.200600120
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Shape, Materials Properties, and Function in Biological Materials Using Laser Speckle Interferometry: In situ Tooth Deformation

Abstract: The manner in which stiff biological objects, such as whole bones and teeth, deform under load can provide direct insight into their in vivo functions, while highlighting the relations between their structure and materials properties. A new approach for studying the mechanical functions of such objects, using as an example the crowns of human teeth, is developed. Tooth‐crown deformation under a compressive load is determined in water using laser speckle interferometry. The deformation patterns are analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 30 publications
1
37
3
Order By: Relevance
“…Another interesting finding of this study was that the enamel cap of minipigs is capable of deforming and rotating at loads as low as 16 N. This finding is very different from that of Zaslansky et al, [27] who showed that the enamel cap of an isolated human premolar did not deform or rotate at loads lower than 80 N. This is most likely related to differences in the structure, mineral content and morphology of the respective enamels. Previous studies comparing human and pig molar crowns have shown that despite overall similarities in morphology, development and function, human teeth have a different enamel microstructure as well as a stiffer, thicker and less complex enamel cap compared to the pig.…”
contrasting
confidence: 86%
See 3 more Smart Citations
“…Another interesting finding of this study was that the enamel cap of minipigs is capable of deforming and rotating at loads as low as 16 N. This finding is very different from that of Zaslansky et al, [27] who showed that the enamel cap of an isolated human premolar did not deform or rotate at loads lower than 80 N. This is most likely related to differences in the structure, mineral content and morphology of the respective enamels. Previous studies comparing human and pig molar crowns have shown that despite overall similarities in morphology, development and function, human teeth have a different enamel microstructure as well as a stiffer, thicker and less complex enamel cap compared to the pig.…”
contrasting
confidence: 86%
“…More recently electronic speckle pattern interferometry (ESPI) has been adapted to the study of whole-tooth mechanical behavior under load, while the tooth is submerged in water. [27] ESPI is a noncontact, nondestructive method that is capable of mapping three-dimensional, nanometer-scale whole surface displacements on an irregular object. The ESPI method is able to detect deformation and rotation but is insensitive to whole body translation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the maximal willing force in humans measured in the posterior region is 500-700 N, it was considered that the force intensity decreases with the teeth loos and depends of muscular strength (Muller et al 2001). The force was applied to the buccal and lingual cusps of loading teeth in both models, across the horizontal extention of the gnatodynamometer (Qian et al 2009;Zaslansky et al 2006). Gnatodynamometer was used for the purpose of precise and controlled force (load) measuring.…”
Section: The Methods and Materialsmentioning
confidence: 99%